Meteorological data from Mälaren - Galten Island, 1999-01-01–2025-12-01 - Erken Laboratory (Uppsala University, 2026)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Erken Laboratory (2026). Meteorological data from Mälaren - Galten Island, 1999-01-01–2025-12-01 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/MRnUdaWGjQL0RLHXHe-ex0So
Keywords: Erken Laboratory; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Incoming shortwave radiation; Incoming shortwave radiation; Photosynthetic Photon Flux Density; Photosynthetic Photon Flux Density; Wind speed; Wind speed; Wind vector; Wind vector; Wind direction; Wind direction; Standard deviation of wind direction; Standard deviation of wind direction; Air pressure; Air pressure; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap